2017
DOI: 10.1162/glep_a_00403
|View full text |Cite
|
Sign up to set email alerts
|

Ratcheting Up Carbon Trade: The Politics of Reforming EU Emissions Trading

Abstract: The EU’s emissions trading system (ETS) covers almost half of its greenhouse gas emissions and has been hailed as the cornerstone and flagship of EU climate policy. In spring 2013, however, the ETS was in severe crisis, with a huge surplus of allowances and a sagging carbon price. Even a formally simple measure to change the timing of auctioning was initially rejected by the European Parliament. Two years later, a much more important, quantity-focused “market thermostat” (the market stability reserve) was adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 22 publications
(26 reference statements)
1
36
0
Order By: Relevance
“…While a full discussion of overallocation and any potential remedies is beyond the scope of this analysis, we note that policymakers have several options to achieve additional emission reductions using the capand-trade program. Potential reforms include reducing the future supply of compliance instruments on a onetime basis; reducing the future supply of compliance instruments using a rule-based adjustment that applies only if observed banking metrics exceed (or market prices fall short of) certain pre-determined levels, as is done for the EU ETS and RGGI programs, respectively [15,32,33]; and increasing the program's minimum floor price to drive additional greenhouse gas reductions in the presence of overallocation conditions. Tracking key program outcomes (MMtCO 2 e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a full discussion of overallocation and any potential remedies is beyond the scope of this analysis, we note that policymakers have several options to achieve additional emission reductions using the capand-trade program. Potential reforms include reducing the future supply of compliance instruments on a onetime basis; reducing the future supply of compliance instruments using a rule-based adjustment that applies only if observed banking metrics exceed (or market prices fall short of) certain pre-determined levels, as is done for the EU ETS and RGGI programs, respectively [15,32,33]; and increasing the program's minimum floor price to drive additional greenhouse gas reductions in the presence of overallocation conditions. Tracking key program outcomes (MMtCO 2 e).…”
Section: Resultsmentioning
confidence: 99%
“…State policymakers have since called for additional reporting metrics to track observed banking behavior in order to evaluate concerns related to overallocation, as is done with other prominent cap-and-trade programs-including the northeastern US states' RGGI program [32], the European Union ETS [33], and even CARB's own Low Carbon Fuel Standard [34]. In October 2018, the Independent Emissions Market Advisory Committee (IEMAC)-an advisory body created by AB 398 that reports to both CARB and the California Legislature, on which one of us serves-concluded that current program reporting is insufficient and recommended CARB adopt metrics for tracking banking on an annual and multi-year compliance period basis [15].…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature tends to focus on the shortcomings of single climate policy measures (such as the emission trading scheme or renewable energy policy in particular) in contributing to climate change mitigation goals, safeguarding the internal energy market and decoupling environmental protection from economic performance (e.g., Flues, Löschel, Lutz, & Schenker, 2014;Gawel, Strunz, & Lehmann, 2014;Helm, 2014;Jevnaker & Wettestad, 2017). The existing literature tends to focus on the shortcomings of single climate policy measures (such as the emission trading scheme or renewable energy policy in particular) in contributing to climate change mitigation goals, safeguarding the internal energy market and decoupling environmental protection from economic performance (e.g., Flues, Löschel, Lutz, & Schenker, 2014;Gawel, Strunz, & Lehmann, 2014;Helm, 2014;Jevnaker & Wettestad, 2017).…”
Section: Policy Context and Contribution To The Literature On The Ementioning
confidence: 99%
“…However, despite rising academic interest in the link between energy and climate policies, we still have limited cumulative knowledge on these political dynamics. The existing literature tends to focus on the shortcomings of single climate policy measures (such as the emission trading scheme or renewable energy policy in particular) in contributing to climate change mitigation goals, safeguarding the internal energy market and decoupling environmental protection from economic performance (e.g., Flues, Löschel, Lutz, & Schenker, 2014;Gawel, Strunz, & Lehmann, 2014;Helm, 2014;Jevnaker & Wettestad, 2017). What is missing is systematic and comparative research on the conditions of policy coherence.…”
Section: Policy Context and Contribution To The Literature On The Ementioning
confidence: 99%
“…The EU ETS is the world's largest greenhouse gas emissions trading system (Point Carbon 2018, p. 3) and has a long policy history, dating back to the late 1990s. During that time, it has undergone a near-continuous process of policy change: since 2003, six major reforms have been adopted (Jevnaker and Wettestad 2017;Skjaerseth and Wettestad 2010). The ETS is a highly complex instrument that creates uneven benefits and costs for a wide range of actors.…”
Section: Introductionmentioning
confidence: 99%